A novel ten-gene prognostic signature for cervical cancer based on CD79B-related immunomodulators - Pu, Dan; Liu, Dan; Li, Can; Chen, Chunyan; Che, Yuxin; Lv, Jiaoyan; Yang, Yang; Wang, Xuelian (Frontiers in Genetics, 2022)
The identification of immune-related prognostic biomarkers provides the possibility of developing new immunotherapy strategies. In this study, we investigated immune-related biomarkers in tumor microenvironment to predict the prognosis of cervical cancer ( CC ) patients. ESTIMATE and CIBERSORT algorithms were used to calculate the abundance of tumor-infiltrating immune cells (TICs) and the amount of immune and stromal components in cervical samples (n=309) from the The Cancer Genome Atlas (TCGA). Afterward, ten immune-related differentially expressed genes (DEGs) associated with CC survival were identified via the intersection analyses of multivariate Cox regression and PPI. CD79B was chosen to analyze its function in immune activities and prognostic value for CC among the ten genes. Further differential expression analysis and the qRT-PCR validation experiment revealed that CD79B expression was down-regulated in CC tissues. Survival analysis suggested that its high expression was associated with the good prognosis of CC patients. In the clinical correlation analysis, CD79B expression was related to primary therapy outcome, race, histological type, degree of differentiation, disease-specific survival, and progression-free interval. GSEA showed that the function and pathway of CD79B were mainly related to immune activities. Meanwhile, CD79B expression was correlated with ten types of TICs. Based on CD79B-associated immunomodulators, an immune prognostic signature consisting of 10 genes (CD96, LAG3, PDCD1, TIGIT, CD27, KLRK1, LTA, PVR, TNFRSF13C, and TNFRSF17) was established and validated to possess good independent prognostic value for CC patients. Finally, a nomogram was successfully built and validated to predict personalized 3- and 5-year survival probabilities in CC patients.